2018
DOI: 10.1007/s00253-018-8898-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel laccase from thermoalkaliphilic bacterium Caldalkalibacillus thermarum strain TA2.A1 able to catalyze dimerization of a lignin model compound

Abstract: In the present study, the gene encoding a multicopper oxidase, more precisely a laccase from the thermoalkaliphilic aerobic bacterium Caldalkalibacillus thermarum strain TA2.A1 (CtLac), was cloned and expressed in Escherichia coli. CtLac is a monomeric protein with a molecular weight of 57 kDa as determined by native polyacrylamide gel electrophoresis. The optimum pH and temperature for 2,6-dimethoxyphenol (2,6-DMP) oxidation were 8.0 and 70 °C, respectively. The kinetic constants K and k for 2,6-DMP were of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 50 publications
4
17
0
Order By: Relevance
“…The blockage of the substrate pathway or the transfer of electrons at the T1 site leads to an inhibition in enzyme activity [ 44 ]. Increased laccase activity in the presence of some metal ions, especially copper, has been observed for most laccases, and this can be interpreted as Cu 2+ filling the type one Copper binding site [ 18 , 27 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blockage of the substrate pathway or the transfer of electrons at the T1 site leads to an inhibition in enzyme activity [ 44 ]. Increased laccase activity in the presence of some metal ions, especially copper, has been observed for most laccases, and this can be interpreted as Cu 2+ filling the type one Copper binding site [ 18 , 27 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Table the most perspective strains are listed. As an example, gene encoding a laccase from a thermophilic aerobic bacteria Caldalkalibacillus thermarum TA2.A1 was cloned and expressed in E. coli [32]. It was found that laccase from this strain was monomeric protein with a molecular weight of 57 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…2.9 retained 80% of its activity after 16 h at 70 • C and after 6 h at 80 • C (Navas et al, 2019). In addition, a novel laccase from the thermoalkaliphilic bacterium Caldalkalibacillus thermarum strain TA2.A1 showed optimum activity at alkaline pH 8.0 and 70 • C, with a half-life of 12 h at 90 • C, pH 8.0 and 6 h at 90 • C, pH 9.0 (Ghatge et al, 2018). Halophilic laccases are also very attractive for biotechnological applications, two examples are a highly thermostable salt/solvent-tolerant laccase from the halophilic archaeon Haloferax volcanii (Uthandi et al, 2010) and the extracellular laccase produced by the halophilic bacterium Aquisalibacillus elongatus (Rezaie et al, 2017).…”
Section: Laccases (Ec 11032)mentioning
confidence: 99%